Prescribing Pattern And Monitoring Of Calcitriol Therapy In A Tertiary Care Medical Center - Reen, A.R.; Morgan, M.M.; Lai, P. (Universiti Sains Malaysia, 2005)
BACKGROUND: Calcitriol has long been shown to be an effective therapy in the management of osteoporosis and renal osteodystrophy.However, it carries the potential risk of causing hypercalcemia and hyperphosphatemia when used without proper monitoring. It is also a costly drug. In recent years, the usage of calcitriol in University Malaya Medical Centre (UMMC) has shown a huge increase.